Intensity and Trustworthiness Awake Delay Perceptive Routing for Submarine WSNs - Devakumar Devakumar; V. Balamurugan (Institute of Advanced Engineering and Science, 2018)
Submarine Wireless Sensor Networks (SWSNs) have earned important concentration of both university and manufacturing in current years. In this paper, we introduce intensity and trustworthiness awake delay perspective (ITADP) routing protocol for submarine WSNs. We get inspiration from Submarine Opportunistic Routing (SOR) protocol that explains expected end-to-end latency from Sender sensor to sink. We consider two faults in SOR. Initially, in SOR protocol, sensor transmit the information to intermediate node that have higher trustworthiness missing the depth of the forwarder node, thus create more hop counts. The coordination time of intermediate sensor cluster is second fault that increases the latency. Thus, we introduce Intensity and trustworthiness awake routing in submarine WSNs.